Nikolaj Serikoff. Arabic Medical Manuscripts of the Wellcome Library. A Descriptive Catalogue of the H˘addad Collection (WMS Arabic 401–487) - Frantsuzov, Sergej A. A. (Acta Orientalia Vilnensia, 2006)
...